PERBANDINGAN PARAMETER FISIOLOGI ANTARA AYAM HUTAN HIJAU (Gallus varius) DAN AYAM KAMPUNG (Gallus gallus domesticus) ASAL PULAU ALOR - Tabelak, Alva Chrisjel; Nitbani, Heny; Utami, Tri (Jurnal Veteriner Nusantara, 2025)
Physiological parameters are one of the indicators to determine the condition of the body and its organ systems, indicating whether they are healthy or experiencing physiological abnormalities and disorders. Examples of physiological parameters include heart rate, respiratory rate, and body temperature. Birds are considered healthy if all organ systems in their bodies are functioning properly, according to the reference data based on physiological parameters. The green junglefowl and native chickens from Alor island are two types of birds that have different habitats and behaviors. This study examines the physiological parameters of these two animals, with the end result being physiological data and statistical comparisons. This physiological data serves as an assesment and knowledge of the condition of green junglefowl and native chickens. Three green junglefowl and three native chickens from Alor island were used in this study. The research was conducted for three consecutive days with measurements taken at 07.00, 12.00 and 18.00. The results showed that the average heart rate, respiratory rate, and body temperature of green junglefowl were higher than those of native chickens. The comparison of research data was analyzed using independent T-test and Mann-Whitney test. The data analysis results showed that there were significant differenses in the data between green junglefowl and native chickens